(untitled) (Research, Society and Development, 2021)
The present preliminary study aims at the rapid quantitative determination of the major chemical elements in the ashes of raw milk samples, using energy dispersive X-ray fluorescence spectrometry. The precision of the method was satisfactory (variation coefficient ≤ 5%). The mean values (in mmol·kg-1) obtained from the analysis of 32 raw milk samples showed good agreement with data from the Brazilian and international literature: K (26.1 ± 4.6), Ca (33.8 ± 3.7), P (28.4 ± 2.7), Na (21 ± 3.3) and Mg (4.7 ± 0.5). Residual Cl concentration (19.0 ± 3.3 mmol·kg-1) was lower than expected due to incineration losses. The results suggest a good application potential of the method for other dairy products.